An in vivo avian model of human melanoma to perform rapid and robust preclinical studies - Loraine Jarrosson; Stéphane Dalle; Clélia Costechareyre; Yaqi Tang; Maxime Grimont; Maud Plaschka; Marjorie Lacourrège; Romain Teinturier; Myrtille Le Bouar; Delphine Maucort‐Boulch; Anaïs Eberhardt; Valérie Castellani; et al. (EMBO Molecular Medicine, 2023)
Abstract Metastatic melanoma patients carrying a BRAFV600 mutation can be treated with a combination of BRAF and MEK inhibitors (BRAFi/MEKi), but innate and acquired resistance invariably occurs. Predicting patient response to targeted therapies is crucial to guide clinical decision. We describe here the development of a highly efficient patient‐derived xenograft model adapted to patient melanoma biopsies, using the avian embryo as a host (AVI‐PDXTM). In this in vivo paradigm, we depict a fast and reproducible tumor engraftment of patient samples within the embryonic skin, preserving key molecular and phenotypic features. We show that sensitivity and resistance to BRAFi/MEKi can be reliably modeled in these AVI‐PDXTM, as well as synergies with other drugs. We further provide proof‐of‐concept that the AVI‐PDXTM models the diversity of responses of melanoma patients to BRAFi/MEKi, within days, hence positioning it as a valuable tool for the design of personalized medicine assays and for the evaluation of novel combination strategies.